Surgery with curative-intent in patients treated with first-line chemotherapy plus bevacizumab for metastatic colorectal cancer First BEAT and the randomised phase-III NO16966 trial - Okines, A (Nature Publishing Group, 2009)
BACKGROUND: Complete resection of metastases can result in cure for selected patients with metastatic colorectal cancer. METHODS: First BEAT evaluated the safety of bevacizumab with first-line chemotherapy in 1914 patients. Prospectively collected data from 225 patients who underwent curative-intent surgery were analysed, including an exploratory comparison of resection rate in patients treated with different regimens. NO16966 compared efficacy of oxaliplatin-based chemotherapy plus bevacizumab or placebo in 1400 patients. A retrospective analysis of resection rate was undertaken. RESULTS: In First BEAT, 225 out of 1914 patients (11.8%) underwent curative-intent surgery at median 64 days (range 42–100) after the last dose of bevacizumab. R0 resection was achieved in 173 out of 225 patients (76.9%). There were no surgery-related deaths and serious post-operative complications were uncommon, with grade 3/4 bleeding and wound-healing events reported in 0.4% and 1.8%, respectively. Resection rates were highest in patients receiving oxaliplatin-based combination chemotherapy (P=0.002), possibly confounded by patient selection. In NO16966, 44 out of 699 patients treated with bevacizumab (6.3%) and 34 out of 701 patients treated with placebo (4.9%) underwent R0 metastasectomy (P=0.24). CONCLUSIONS: The rate of serious post-operative complications in First BEAT was comparable to historical controls without bevacizumab. In NO16966, there were no statistically significant differences in resection rates or overall survival in patients treated with bevacizumab vs placebo.